Hepatoprotective Effect of Carob Pulp Flour (Ceratonia siliqua L.) Extract Obtained by Optimized Microwave-Assisted Extraction - Nikola Martić; Jana Zahorec; Nebojša Stilinović; Bojana Andrejić-Višnjić; Branimir Pavlić; Nebojša Kladar; Dragana Šoronja-Simović; Zita Šereš; Miodrag Vujčić; Olga Horvat; Aleksandar Rašković (MDPI AG, 2022)
To examine antioxidant capacity and the hepatoprotective effect of carob pulp flour, microwave-assisted extraction was performed. The influence of ethanol concentration (0-40% w/w), extraction time (5-25 min) and irradiation power (400-800 W) on DPPH, FRAP and ABTS antioxidant activity of carob pulp flour extract was evaluated. The strongest influence was that of the ethanol concentration, followed by extraction time. Optimal process parameters for maximizing total antioxidant activity were determined, using response surface methodology: ethanol concentration 40%, time 25 min and power 800 W. Carob extract obtained at optimal conditions (CE) was analyzed in vivo using a paracetamol-induced hepatotoxicity model in mice. Treatment with CE attenuated the parameters of liver injury, especially aspartate and alanine aminotransferase activity, and prevented paracetamol-induced increase in malondialdehyde levels. Pretreatment with CE reversed the activities of superoxide dismutase, catalase, glutathione peroxidase and glutathione S-transferase enzymes after the high dose of paracetamol in the liver. Hepatotoxicity induced using a toxic dose of paracetamol was also seen through histopathological alterations, which were significantly reduced in the groups treated with CE prior to paracetamol. Still, the number of Kupffer cells and macrophages did not differ among groups. Finally, pretreatment of mice with CE and paracetamol significantly decreased the expression of cytochrome P450 2E1 (CYP2E1) in hepatocytes.